A hybrid approach for the personalisation of cloud-based e-governance services. (1st January 2013) - Do, Quynh Ngoc Thuy; Hussain, Farookh Khadeer
Cloud computing is a new and promising paradigm for service delivery (including computing resources) over the internet. Cloud computing standards and architecture play an important role in benefiting governments by reducing operating costs and increasing governance effectiveness. Cloud-based e-governance contributes to managing security, reducing cost based on a pay-as-you-go method, IT labour cost reduction, and increasing scalability. Given the importance of cloud computing in the today's emerging technologies, personalisation in cloud computing is also significant in supporting users to obtain what they need without being required to request it explicitly. This research will focus mainly on a personalisation algorithm to for cloud computing. A case study in which a user can suggest the language they want to use without making an explicit request will be provided to assist further understanding of the new algorithm, which is a combination of the TOPSIS and Pearson correlation coefficient methods.